PENGGUNAAN KOMPOSISI MEDIA TANAM ARANG SEKAM, COCOPEAT DAN ZEOLIT PADA SISTEM IRIGASI TETES TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON - Ezperanza, Putri; Suryadi, Edy; Amaru, Kharistya (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
The right planting medium will help produce good growth and yields. The purpose of this study was to determine the use of planting media using a drip irrigation system on the growth and yield of melon plants. The research method used was experimental using Rancangan Acak Lengkap (RAL). Treatment in this study consisted of P1 (chaff charcoal and cocopeat), P2 (cocopeat and zeolite), and P3 (husk charcoal and zeolite) with a composition of 50%:50%. Results showed that there was an effect of using cocopeat, husk charcoal, and zeolite planting media on the number of leaves, stem diameter, fruit weight, fruit water content, level of fruit sweetness, and plant height. Cocopeat and zeolite (50%:50%) growing media gave the best growth and yield, tem diameter with a final thickness of 11mm, the final number of leaves was 42 leaves, average fruit weight was 1.3kg, the highest fruit moisture content was 92% and level of sweetness highest 15 brix.